Utilization of agricultural residues from monascus fermentation - Eadmusik, Sunee (Asia-Pacific Journal of Science and Technology, 2017)
Monascusspecies have been used in food processing for a long time. During fermentation, Monascus species can produce pigments which varied from yellow to red color, Monacolin K and GABA which are health beneficial substances. Mycotoxin namely Citrinin is also produced during Monascus fermentation. There are factors affecting Monascus-fermented products such as fermenting conditions, Monascus strain and type of substrate used. Traditionally, rice was used as a substrate for Monascusfermentation. Recently, value adding of agricultural residues by Monascus fermentation is of great interest to researchers. This review illustrates the research works on Monascusfermentation and its obtained products, agricultural exploitation of residues as a substrate in food products.